Mono and Double-Decker Lutetium Phthalocyanines Bearing Iodine Groups: Electrochemical and Electrochromic Properties - ÖZKAYA, ALİ RIZA; ORMAN, EFE BATURHAN (ELECTROCHEMICAL SOC INC, 2016)
In this study, novel mono 1b (LuPc) and double-decker 1c (LuPc2) lutetium(III) phthalocyanine (Pc) complexes carrying iodine groups have been synthesized and their electrochemical, in-situ spectroelectrochemical, and in-situ electrocolorimetric properties were studied and compared in solution. Electrochemically produced species of 1c displayed distinct spectral and color changes. Thus, spectroelectrochemical and electrocolorimetric measurements of cast film of 1c on indium-tin oxide (ITO) glass were also performed in aqueous solution with the aim of evaluating its applicability as an electrochromic material. ITO/LuPc2 1c cast film illustrated distinct and reversible green to yellow, green to light blue and light blue to purple color changes due to the electrochemically generated anionic and cationic forms. The film showed high optical and coulombic stabilities and especially high optic contrast during the oxidation process. The response time was also found to be satisfactorily fast for the transitions between green and yellow colors. The results showed that 1c has the potential for usage as an efficient material in electrochromic devices. (C) 2016 The Electrochemical Society. All rights reserved.
Keywords: RARE-EARTH COMPLEXES; METAL-FREE; SUBSTITUENTS; SPECTROELECTROCHEMISTRY; PORPHYRINATO; SPECTROSCOPY; LIGANDS; ZN(II)